Early cortisol values and long-term outcomes in extremely low birth weight infants - Aucott, SW (2009)
OBJECTIVE: Both excess and insufficient levels of glucocorticoid in extremely low birth weight (ELBW) infants have been associated with adverse hospital outcomes, whereas excess glucocorticoid exposure has been associated with long-term adverse neurodevelopment. Our objective was to evaluate the relationship between neonatal cortisol concentrations and long-term outcomes of growth and neurodevelopment. STUDY DESIGN: As part of a multicenter randomized trial of hydrocortisone treatment for prophylaxis of relative adrenal insufficiency, cortisol concentrations were obtained at 12 to 48 h of postnatal age and at days 5 to 7 on 350 intubated ELBW infants, of whom 252 survived and returned for neurodevelopmental follow-up at 18 to 22 months corrected age. Cortisol values from each time point were divided into quartiles. Growth and neurodevelopmental outcome were compared for each quartile. RESULT: Median cortisol value was 16.0 μg per 100 ml at baseline for all infants, and 13.1 μg per 100 ml on days 5 to 7 in the placebo group. Outcomes did not differ in each quartile between treatment and placebo groups. Low cortisol values at baseline or at days 5 to 7 were not associated with impaired growth or neurodevelopment at 18 to 22 months corrected age. High cortisol values were associated with an increase in cerebral palsy, related to the increased incidence of severe intraventricular hemorrhage (IVH) and periventricular leukomalacia. CONCLUSION: Low cortisol concentrations were not predictive of adverse long-term outcomes. High cortisol concentrations, although predictive of short-term adverse outcomes such as IVH and periventricular leukomalacia, did not additionally predict adverse outcome. Further analysis into identifying factors that modulate cortisol concentrations shortly after birth could improve our ability to identify those infants who are most likely to benefit from treatment with hydrocortisone.